2) Calculeaza :
a) ( 2 +√3 )² =
b) ( 1 +√2)² =
c) (√5 + 2 )²=
e) (√3 - 2 ) ² =
f) ( 2 - √2 )² =
g) ( 3 - √3 )² =
h) ( 3√2 - 1 ) ² =
i) ( 1 + √3 ) ( 1 - √3 ) =
j ) ( 3 √2 - 1 ) ( 3 √2 + 1 ) =
k) (√3 + 5 ) ( 5 - √3 ) =
l) ( 2√2 - 3 ) ( 2√2 + 3 )=

1

Răspunsuri

2014-11-18T15:46:40+02:00
A) 4 + 4√3 + 3 = 7 + 4√3
b) 1 + 2√2 +2 = 3 + 2√2
c) 5 + 4√5 + 4 = 9 + 4√5
e) 3 - 4√3 + 4 = 7 - 4√3
 f) 4 - 4√2 + 2 = 6 - 4√2
g) 9 - 6√3 + 3 = 12 - 6√3
h) 18 - 6√2 +1 = 19 - 6√2
l)  1 - 3 = - 2
j) 18 -1 = 17
k) 25 - 3 = 22
l) 8 - 9 = - 1